Dielectric and gas adsorption/desorption properties of x-Li(Pc) having one-dimensional channels surrounded by Pc˙− columns. Issue 44 (27th October 2020) - Nishi, Miki; Hoshino, Norihisa; Noro, Shin-ichiro; Fujimoto, Hitoshi; Akutagawa, Tomoyuki; Matsuda, Masaki
Abstract : A one-dimensional channel system x -Li(Pc), composed of π-radical Pc˙ −, was investigated. It was revealed that this channel surrounded by Li(Pc) columns is flexible, and gas adsorption/desorption measurements showed selective properties. Abstract : A one-dimensional channel system x -Li(Pc), composed of π-radical Pc˙ −, was investigated. Crystal structure analysis revealed that this channel surrounded by Li(Pc) columns is flexible, and gas adsorption/desorption measurements showed selective adsorption/desorption properties. Along with Li + motion, specific dielectric properties induced by a guest species within the channel were also observed.